Mitochondrial mosaics in the liver of 3 infants with mtDNA defects - Roels, Frank (BioMed Central, 2009)
BACKGROUND: In muscle cytochrome oxidase (COX) negative fibers (mitochondrial mosaics) have often been visualized. METHODS: COX activity staining of liver for light and electron microscopy, muscle stains, blue native gel electrophoresis and activity assays of respiratory chain proteins, their immunolocalisation, mitochondrial and nuclear DNA analysis. RESULTS: Three unrelated infants showed a mitochondrial mosaic in the liver after staining for COX activity, i.e. hepatocytes with strongly reactive mitochondria were found adjacent to cells with many negative, or barely reactive, mitochondria. Deficiency was most severe in the patient diagnosed with Pearson syndrome. Ragged-red fibers were absent in muscle biopsies of all patients. Enzyme biochemistry was not diagnostic in muscle, fibroblasts and lymphocytes. Blue native gel electrophoresis of liver tissue, but not of muscle, demonstrated a decreased activity of complex IV; in both muscle and liver subcomplexes of complex V were seen. Immunocytochemistry of complex IV confirmed the mosaic pattern in two livers, but not in fibroblasts. MRI of the brain revealed severe white matter cavitation in the Pearson case, but only slight cortical atrophy in the Alpers-Huttenlocher patient, and a normal image in the 3rd. MtDNA in leucocytes showed a common deletion in 50% of the mtDNA molecules of the Pearson patient. In the patient diagnosed with Alpers-Huttenlocher syndrome, mtDNA was depleted for 60% in muscle. In the 3rd patient muscular and hepatic mtDNA was depleted for more than 70%. Mutations in the nuclear encoded gene of POLG were subsequently found in both the 2nd and 3rd patients. CONCLUSION: Histoenzymatic COX staining of a liver biopsy is fast and yields crucial data about the pathogenesis; it indicates whether mtDNA should be assayed. Each time a mitochondrial disorder is suspected and muscle data are non-diagnostic, a liver biopsy should be recommended. Mosaics are probably more frequent than observed until now. A novel pathogenic mutation in POLG is reported. Tentative explanations for the mitochondrial mosaics are, in one patient, unequal partition of mutated mitochondria during mitoses, and in two others, an interaction between products of several genes required for mtDNA maintenance.